Experimental Investigation of the Threshold Pressure Gradient on Saturated/Unsaturated Flow in the Ultra-low Permeability Reservoirs - Xie, Sam; He, S.; Jiao, C.; Zhu, H.; Fu, C.; Lei, G. (2011)
According to the investigation argument between Chinese researchers and oversea scholars on threshold pressure gradient characteristics in ultra-low permeability reservoirs，with full diameter from Triassic outcrop by means of fully-automatic flooding system of AFS300TM provided by Core Lab in USA，an unsteady approach to test the threshold pressure gradient of saturated and unsaturated flow in the ultra-low permeability cores is proposed. The threshold pressure gradient in the saturated and unsaturated flows are analyzed with the investigation on the pressure variation from downstream and upstream of the rock cores. The experimental results indicate that the threshold pressure gradient doesn′t exist in the ultra-low permeability rocks with saturated flow of normal brine and kerosene. And the capillary force caused in the interfaces of the fluids in the unsaturated flow is the basic reason of obvious threshold pressure gradient. Moreover，the dynamic effect of capillary pressure is observed in the unsteady state flow experiments from ultra-low permeability rocks.